2020
DOI: 10.1186/s12893-020-00751-6
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of intraoperative neurological monitoring for esophageal cancer with double aortic arch; a case report

Abstract: Background: Double aortic arch (DAA) is a congenital anomaly of the aorta. Esophageal cancer with DAA is rare, and consequently, the appropriate surgical approach has not been standardized. Herein, we report the utilization of intraoperative neurological monitoring (IONM) system to preserve the function of the recurrent laryngeal nerve. Case presentation: A 79-year-old man with esophageal cancer was diagnosed with DAA incidentally. The descending aorta was located on the right side of the thoracic vertebrae. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In literature, the use of IONM is also recommended in patients with anatomical laryngeal alterations because of its reliability in high‐risk cases during revision surgery with the loss of the anatomical landmarks 10 , 11 , 14 , 15 , 16 but it has never been described the use of IONM in case of thyroid surgery in patients with a clinical history of partial laryngeal resection. In such scenarios, the preservation of the remaining RLN after partial laryngectomy is mandatory because any injury would lead to the loss of the laryngeal functions with consequent need of total laryngectomy or permanent tracheostomy and/or gastrostomy.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, the use of IONM is also recommended in patients with anatomical laryngeal alterations because of its reliability in high‐risk cases during revision surgery with the loss of the anatomical landmarks 10 , 11 , 14 , 15 , 16 but it has never been described the use of IONM in case of thyroid surgery in patients with a clinical history of partial laryngeal resection. In such scenarios, the preservation of the remaining RLN after partial laryngectomy is mandatory because any injury would lead to the loss of the laryngeal functions with consequent need of total laryngectomy or permanent tracheostomy and/or gastrostomy.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the heart's location in the left thorax interrupted middle to lower mediastinal dissection, in contrast to a typical right thoracic approach. Mushiake et al [11] judged that a more familiar method is suitable for that atypical case, so they selected right thoracotomy in the prone position. Kumar et al [12] reported that the right arch of the DAA of their patient was a nondominant arch.…”
Section: Choice Of Surgical Methodsmentioning
confidence: 99%
“…In our case, we chose the right thoracic approach in the lateral position because the tumor was located in the mid-thoracic esophagus. The first step was the dissection of upper mediastinal LNs and confirmation of the location of the bilateral RLN using cervical mediastinoscopy, which was similar to the method of Mushiake [11]. The inflatable mediastinoscope we use is an improvement based on Fujiwara's [22] method of using mediastinoscopy, which is different from that of Mushiake.…”
Section: Choice Of Surgical Methodsmentioning
confidence: 99%
See 2 more Smart Citations